Analysis Robbery from a Criminal Law Perspective: Law Enforcement, Criminal Accountability, and the Effectiveness of Sanctions - Farhan Fathur Rahman; Zahara Qifta Isvara (AT-TAFAHUM: Journal of Law, 2025)
This study aims to analyze the crime of robbery from a criminal law perspective, with a focus on law enforcement, criminal liability, and the effectiveness of criminal sanctions. The background of this study is based on the increasing crime rate, especially robbery, which not only causes property damage but also threatens the safety and security of the community. This study uses a normative juridical method with a statutory and conceptual approach, and is supported by literature and documentation studies of primary and secondary legal materials. The research stages include data collection, data reduction, data presentation, and normative analysis of applicable legal provisions, especially Article 365 of the Criminal Code (KUHP). The results of the study indicate that normatively, the regulation regarding robbery has been strictly regulated with severe criminal threats, however, in practice, law enforcement still faces various obstacles, such as weak evidence, limited apparatus resources, and inconsistencies in judges' decisions